Risperidone Mitigates Enhanced Excitatory Neuronal Function and Repetitive Behavior Caused by an ASD-Associated Mutation of SIK1 - Badawi, Moataz; Mori, Takuma; Kurihara, Taiga; Yoshizawa, Takahiro; Nohara, Katsuhiro; Kouyama-Suzuki, Emi; Yanagawa, Toru; Shirai, Yoshinori; Tabuchi, Katsuhiko (Frontiers in Molecular Neuroscience, 2021)
Six mutations in the salt-inducible kinase 1 (SIK1)-coding gene have been identified in patients with early infantile epileptic encephalopathy (EIEE-30) accompanied by autistic symptoms. Two of the mutations are non-sense mutations that truncate the C-terminal region of SIK1. It has been shown that the C-terminal-truncated form of SIK1 protein affects the subcellular distribution of SIK1 protein, tempting to speculate the relevance to the pathophysiology of the disorders. We generated SIK1-mutant (SIK1-MT) mice recapitulating the C-terminal-truncated mutations using CRISPR/Cas9-mediated genome editing. SIK1-MT protein was distributed in the nucleus and cytoplasm, whereas the distribution of wild-type SIK1 was restricted to the nucleus. We found the disruption of excitatory and inhibitory (E/I) synaptic balance due to an increase in excitatory synaptic transmission and enhancement of neural excitability in the pyramidal neurons in layer 5 of the medial prefrontal cortex in SIK1-MT mice. We also found the increased repetitive behavior and social behavioral deficits in SIK1-MT mice. The risperidone administration attenuated the neural excitability and excitatory synaptic transmission, but the disrupted E/I synaptic balance was unchanged, because it also reduced the inhibitory synaptic transmission. Risperidone also eliminated the repetitive behavior but not social behavioral deficits. These results indicate that risperidone has a role in decreasing neuronal excitability and excitatory synapses, ameliorating repetitive behavior in the SIK1-truncated mice.